Neuroinflammation and сhemotherapy-induced peripheral neuropathy - P. I. Pilipenko; V. E. Voytsitsky; Yu. A. Dobresko (Сибирский научный медицинский журнал)
Neurotoxicity is one of the common side effects of anticancer chemotherapy. This pathology has a detectability of 38–90%. In some cases, it causes not only a significant decrease of life quality but also decrease of dose of cytostatics. Therefore, the tasks of early diagnosis, prevention and treatment of neurotoxicity are very relevant. Sensors underlying detection, especially neuroinflammation processes, are needed to develop an effective therapy for chemotherapy-induced neurotoxicity. The purpose of this topic is to study the results of chemotherapy studies on changes in the activity of proinflammatory cytokines. In this regard, the study of behavioral societies in neuropathic pain in animal models is of great importance. It was revealed that various manifestations of inflammation of pro-inflammatory cytokines, chemokines, damage to the dorsal ganglion or distal nerve endings are increasingly being detected. Detection of chemically induced peripheral neuropathy using animal models is necessary for in-depth identification of the cause-and-effect mechanisms of its development and selection of new, more effective methods of treatment.